Total body iron overload in welder's siderosis. Issue 1 (22nd December 2003) - Doherty, M J; Healy, M; Richardson, S G; Fisher, N C
Abstract : Welder's siderosis occurs as a consequence of the inhalation of iron dust. The iron overload of welder's siderosis is usually considered to be confined to the lungs. Here we present three proven cases of welder's siderosis associated with evidence of increased total systemic iron stores, as evidenced by increased serum ferritin levels. Multiple investigations including molecular genotyping for the common mutations found in genetic haemochromatosis failed to prove this was due to haemochromatosis, nor was there any evidence of any other recognised cause of systemic iron overload. Thus the systemic iron overload described seems likely to be due to either occupational exposure, an uncharacterised genetic haemochromatosis, or a combination of both.